Biotechnological Applications of Microalgal Oleaginous Compounds: Current Trends on Microalgal Bioprocessing of Products - Mutanda, T.; Naidoo, D.; Bwapwa, J. K.; Anandraj, A. (Frontiers in Energy Research, 2020)
The microalgal biotechnology industry is expanding rapidly and currently gaining attention due to multiple availabilities of high-value products such as pigments, carbohydrates, proteins, nutraceuticals, biopharmaceuticals, and unique oleaginous compounds fractionated by biomass biorefinery. Microalgae are efficient primary producers in the terrestrial and marine biotopes. They are major sources of global oxygen and are gaining topical prominence due to their concomitant role in the phycoremediation of wastewater effluents and biomass production. Despite their minuscule size, microalgae critically contribute to climate change mitigation through carbon fixation and play a major role in bioenergy applications. Furthermore, carotenoids and phycobiliproteins are the main accessory light-harvesting complexes in microalgae and cyanobacteria. The topical biomedical and pharmaceutical applications of microalgae include anticancer, antidiabetic, antiHIV, antimalarial, antimicrobial, inter alia. The endowment of unique indigenous microalgae and utilization of these biological resources must be harnessed by the biorefinery industry to exploit microalgal biomass opportunities. Therefore, this manuscript factually and critically explores the current status of the biorefinery approach, topical biomedical and pharmaceutical applications, biofuel applications, genetic manipulation of microalgae for enhancement of product yield, challenges and presents prospects, pros and cons, and outlook of the microalgal biotechnology industry.